Elimination effects of toxic trans-crotonaldehyde in mitochondria of glioma by lithocholic acid. Issue 2 (7th February 2019) - Su, Yanbin; Sun, Chengyu; Jiang, Ning; Zhang, Qingsong
Abstract: The purposes of this study were to explore the factors contributing to the generation of the toxic trans-crotonaldehyde in mitochondria of glioma and to look for the elimination effects of the toxic trans-crotonaldehyde by the lithocholic acid. Ultraviolet-visible absorption spectroscopy and mitochondrial isolation and extraction from glioma were used in this study. Research findings showed that the factors contributing to the generation of the toxic trans-crotonaldehyde were hydrogen peroxide, mitochondria of glioma, and their appropriate interaction, respectively. The appropriate quantity of the toxic trans-crotonaldehyde could be induced by hydrogen peroxide (0.16 mmol), mitochondria of glioma (3 mg protein/ml), and 30 min of their interaction, respectively. The most suitable conditions for the lithocholic acid to eliminate the toxic trans-crotonaldehyde were the weakly alkaline of mitochondria of glioma (pH 8.0), the lithocholic acid (0.15 mmol), and 15 min of interaction, respectively. The conclusion was that the lithocholic acid efficiently eliminated the toxic trans-crotonaldehyde in mitochondria of glioma in real time and opened up a new way to treat glioma.